Growth enhancement and resistance of banana plants to fusarium wilt disease as affected by silicate compounds and application frequency - Zakaria, Md Aiman Takrim; Sakimin, Siti Zaharah; Ismail, Mohd Razi; Ahmad, Khairulmazmi; Kasim, Susilawati (Multidisciplinary Digital Publishing Institute, 2024)
The amendment of soils with silicate (Si) compounds is essential to promote growth performance and control Fusarium wilt disease in bananas. Two successive greenhouse trials were conducted at the experimental farm of the University of Putra Malaysia. The treatments were arranged in split plots using a randomized complete block design (RCBD) with four replicates to investigate the effects of Si compounds and application frequency on controlling FOC. Si compounds were used at a constant concentration of 0.1%: T0 (control), T1 (13% SiO2:20% K2O), T2 (26.6% SiO2:13.4% K2O) and T3 (36.2% SiO2:17% Na2O). There were three application frequencies by day intervals (DI): 0DI (without any application), 7DI (12× within 12 weeks after transplanting (WAT)), 15DI (6× within 12 WAT) and 30DI (3× within 12 WAT). From these findings, we observed that the photosynthesis rate started to increase from 10.6 to 19.4 µmol CO2 m−2s−1, when the total chlorophyll content started to increase from 3.85 to 7.61 mgcm−2. The transpiration rate started to increase from a value of 1.94 to 4.31 mmol H2O m−2s−1, when the stomata conductance started to increase from 0.237 to 0.958 mmol m−2s−1. The proline content started to increase from 22.89 to 55.07 µmg−1, when the relative water content started to increase from 42.92 to 83.57%.